Preserving Local Wisdom through Subak Analogy Videos for Teaching Computer Network Concepts - Mertayasa, I Negah Eka; Agustini, Ketut; Wahyudi, Wahyudi; Pradnyana, Ketut Andika; Angoy, Raisalam D; Ozsen, Zeynep (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
This study aims to identify the usefulness of subak analogy videos for learning computer network concepts and to analyze the effectiveness of their use based on students' experiences and understanding. This study uses a qualitative approach with a naturalistic type. Data were collected through observation, in-depth interviews, and documentation of 43 vocational high school students studying computer network concepts. Data analysis was carried out using the Miles and Huberman model, which includes data reduction, data presentation, and concluding. The study results showed that subak analogy videos were beneficial for students in understanding computer network concepts. Students expressed that subak analogies provide a concrete picture of data flow in computer networks, making them easier to understand than conventional approaches. In addition, data analysis showed increased student understanding, as demonstrated by their reflections in discussions and problem-solving based on computer network concepts. These findings indicate that using subak analogy videos can be an effective learning strategy in improving students' understanding of computer network concepts.